Genome-wide association study provides strong evidence of genes affecting the reproductive performance of Nellore beef cows - Pinto De Melo, Thaise [UNESP]; De Camargo, Gregório Miguel Ferreira; De Albuquerque, Lucia Galvão [UNESP]; Carvalheiro, Roberto [UNESP] (Public Library of Science (PLoS), 2017)
Reproductive traits are economically important for beef cattle production; however, these traits are still a bottleneck in indicine cattle since these animals typically reach puberty at older ages when compared to taurine breeds. In addition, reproductive traits are complex phenotypes, i.e., they are controlled by both the environment and many small-effect genes involved in different pathways. In this study, we conducted genome-wide association study (GWAS) and functional analyses to identify important genes and pathways associated with heifer rebreeding (HR) and with the number of calvings at 53 months of age (NC53) in Nellore cows. A total of 142,878 and 244,311 phenotypes for HR and NC53, respectively, and 2,925 animals genotyped with the Illumina Bovine HD panel (Illumina®, San Diego, CA, USA) were used in GWAS applying the weighted single-step GBLUP (WssGBLUP) method. Several genes associated with reproductive events were detected in the 20 most important 1Mb windows for both traits. Significant pathways for HR and NC53 were associated with lipid metabolism and immune processes, respectively. MHC class II genes, detected on chromosome 23 (window 25-26Mb) for NC53, were significantly associated with pregnancy success of Nellore cows. These genes have been proved previously to be associated with reproductive traits such as mate choice in other breeds and species. Our results suggest that genes associated with the reproductive traits HR and NC53 may be involved in embryo development in mammalian species. Furthermore, some genes associated with mate choice may affect pregnancy success in Nellore cattle.